Beneficial and adverse effects of vitamin E on the kidney - Baltusnikiene, Aldona; Staneviciene, Inga; Jansen, Eugène (Frontiers in Physiology, 2023)
This article reviews the beneficial and adverse effects of high-dose vitamin E supplementation on the vitamin E status and renal function in human and rodent studies. The high doses of vitamin E, which can cause renal effects, were compared to upper limits of toxicity (UL) as established by various authorities worldwide. In recent mice studies with higher doses of vitamin E, several biomarkers of tissue toxicity and inflammation were found to be significantly elevated. In these biomarker studies, the severity of inflammation and the increased levels of the biomarkers are discussed together with the need to re-evaluate ULs, given the toxic effects of vitamin E on the kidney and emphasizing oxidative stress and inflammation. The controversy in the literature about vitamin E effects on the kidney is mainly caused by the dose-effects relations that do not give a clear view, neither in human nor animals studies. In addition, more recent studies on rodents with new biomarkers of oxidative stress and inflammation give new insights into possible mechanisms. In this review, the controversy is shown and an advice given on the vitamin E supplementation for renal health.